Fractional carbon dioxide laser versus low-dose UVA-1 phototherapy for treatment of localized scleroderma: a clinical and immunohistochemical randomized controlled study. Issue 8 (November 2016) - Shalaby, S.; Bosseila, M.; Fawzy, M.; Abdel Halim, D.; Sayed, S.; Allam, R.
Abstract Morphea is a rare fibrosing skin disorder that occurs as a result of abnormal homogenized collagen synthesis. Fractional ablative laser resurfacing has been used effectively in scar treatment via abnormal collagen degradation and induction of healthy collagen synthesis. Therefore, fractional ablative laser can provide an effective modality in treatment of morphea. The study aimed at evaluating the efficacy of fractional carbon dioxide laser as a new modality for the treatment of localized scleroderma and to compare its results with the well-established method of UVA-1 phototherapy. Seventeen patients with plaque and linear morphea were included in this parallel intra-individual comparative randomized controlled clinical trial. Each with two comparable morphea lesions that were randomly assigned to either 30 sessions of low-dose (30 J/cm2 ) UVA-1 phototherapy (340–400 nm) or 3 sessions of fractional CO2 laser (10, 600 nm-power 25 W). The response to therapy was then evaluated clinically and histopathologically via validated scoring systems. Immunohistochemical analysis of TGF-ß1 and MMP1 was done. Patient satisfaction was also assessed. Wilcoxon signed rank test for paired (matched) samples and Spearman rank correlation equation were used as indicated. Comparing the two groups, there was an obvious improvement with fractional CO2 laser that was superior to that of low-dose UVA-1 phototherapy. Statistically, there was a significant difference in the clinical scores (p  = 0.001), collagen homogenization scores (p  = 0.012), and patient satisfaction scores (p  = 0.001). In conclusion, fractional carbon dioxide laser is a promising treatment modality for cases of localized morphea, with proved efficacy of this treatment on clinical and histopathological levels.